Development of whey protein-derived aerogel microcarriers for cultivated meat production - Da Hyeon Yang; In-Hwan Lee; Woo-Ju Kim (Food Chemistry, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Achieving BT.2020 red emission with narrowband deep-red iridium complexes in OLEDs - Gyeong Seok Lee; Woo Jin Jeong; Huanyu Zhou; Hyun-Wook Kim; Da In Kim; Kwan-Nyeong Kim; Dong-Hyeok Kim; Thi Na Le; Seungyeon Cho; Jongchan Kim; Tae-Woo Lee; Yun-Hi Kim (Chemical Engineering Journal, 2026)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Evaluation of various mushroom-based scaffolds for application to cellular agriculture - Da Hyeon Yang; In-Hwan Lee; Woo-Ju Kim (Food Chemistry, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Effects of exogenous L-glutamic acid and supplemental LED lighting on the growth and yield of Paprika - Yong Beom Kwon; Joo Hwan Lee; Min Ji Kim; Da Young Lee; In-Lee Choi; Hyuk Sung Yoon; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2025)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Comparison of biogenic volatile organic compounds emissions from representative urban tree species in South Korea and evaluation of standard emission rate models - Da-Hyun Baek; Ye-Bin Seo; Seong-Ji Yu; In-Young Choi; Sang-Woo Lee; Youn-Suk Son; Trieu-Vuong Dinh; Jo-Chun Kim (Atmospheric Environment, 2024)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

The First Record of Ocypode sinensis (Decapoda: Ocypodidae) from the Korean Peninsula: How the Complete Mitochondrial Genome Elucidates the Divergence History of Ghost Crabs - Da-In Kim; Sook-Jin Jang; Taewon Kim (Journal of Marine Science and Engineering, 2023)
Ghost crabs, as a species of the Ocypode within the subfamily Ocypodinae, are distributed in the upper intertidal zone worldwide and are ecologically remarkable. They play an important role in the energy circulation in the intertidal zone and are used as an ecological indicator to predict the impacts of environmental change or anthropogenic activities on the marine ecosystem. In this study, we provide the first evidence for the distribution of O. sinensis in Jeju Island and the southern coastal area on the Korean Peninsula. We generated a high-fidelity mitochondrial genome (mitogenome) for the species. The mitogenome was assembled into a circular chromosome of 15,589 bp, including 13 protein-coding genes, two ribosomal RNA genes, and twenty-two transfer RNA genes. High genetic variation compared with closely related species enabled the precise reconstruction of phylogenetic relationships and an estimation of the divergence times among the Ocypode species. The phylogenetic inference indicated that O. sinensis forms a monophyletic clade with O. cordimanus and diverged from ancestral species approximately 20.41 million years ago.

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Significant relationship between Arctic warming and East Asia hot summers - Da‐Seul Kim; Sang‐Yoon Jun; Myong‐In Lee; Jong‐Seong Kug (International Journal of Climatology, 2022)
Arctic warming is of growing interest because it could affect midlatitude climates. Even though numerous studies have paid attention to the relationship between Arctic warming and the midlatitude climate in winter, the influence of Arctic warming on the summer conditions has not been examined in depth. Here we identify a significant relationship between East Asia hot summers and Arctic warming over the Barents and Kara seas. To represent Arctic warming, we define a combined index by simply differencing the normalized surface air temperature and sea‐ice indices. We found that the combined index in July has significantly high correlations with the temperatures in China, Korea, and Japan. While the teleconnection mechanism is not completely revealed, it is evident that warming over the Barents and Kara seas is accompanied by the local development of an anomalous anticyclone and downstream wave trains, which yield a strong anticyclonic circulation over East Asia and the North Pacific. The anticyclonic circulation persists and intensifies until August, which leads to hot summer conditions in East Asia with warm advection and enhanced shortwave radiation. Our results suggest that Arctic climate conditions can be used as a useful precursor of East Asia temperature variations even in summer.

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

Chemotactic effect of S100A8 and S100A9 on human eosinophilic leukemia cells, EoL-1 through TLR4 - Ayoung Gu; Da Hye Kim; Na Rae Lee; In Sik Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2018)

Effect of house dust mite on neutrophil apoptosis by cytokine secretion in lymphocytes - Na Rae Lee; Ji-Sook Lee; Seung Yeop Baek; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Soo Jin Lee; In Sik Kim (Molecular & Cellular Toxicology, 2016)

House dust mite allergen suppresses neutrophil apoptosis by cytokine release via PAR2 in normal and allergic lymphocytes - Na Rae Lee; Seung Yeop Baek; Ayoung Gu; Da Hye Kim; Seong Yeol Kim; Ji-Sook Lee; In Sik Kim (Immunologic Research, 2016)

Benzo(a)pyrene represses melanogenesis in B16F10 mouse melanoma cells - Da Hye Joo; Hwa Jun Cha; Karam Kim; Minhee Jung; Jung Min Ko; In Sook An; Sung Nae Lee; Hyun Hee Jang; Seunghee Bae; Nam Kyung Roh; Kyu Joong Ahn; Sungkwan An (Molecular & Cellular Toxicology, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

Effects of phenotypic and RAPD variations on ecophysiological characterization of reeds (Phragmites australis) in Suncheon Bay - In Seon Jeon; Da Som Kwon; Hoon Shin; Won Bok Kim; Na Roo Kang; Sun Mi Whang; Mi Sun Kim; Soo Jin Wi; Ky Young Park (Journal of Plant Biology, 2015)

Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Jun Hyung Seo; Hyo Geun Bae; Da Hee Park; Beom Seok Kim; Jong Wook Lee; Jung In Lee; Dong Hyun Kim; Seok Won Lee; Bong Bo Seo (Genes & Genomics, 2013)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)